Peran Literasi Keuangan, Harga, Dan Promosi Penjualan Pada Perilaku Konsumtif Generasi Z - Moh. Zaki Kurniawan (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
This research intends to determine the influence of financial literacy, price, and sales promotion on the consumptive behavior of Generation Z. Purpose sampling technique is used to take samples from Generation Z in Blitar Regency. This study uses ordinary least squares to determine the effect of financial literacy, price, and sales promotion on the consumptive behavior of Generation Z. The research shows that financial literacy does not have an influence on the consumptive behavior of Generation Z. Prices and sales promotions influence the consumptive behavior of Generation Z. For financial literacy, price, and sales promotion simultaneously influence the consumptive behavior of generation Z.